MODEL DEFORMASI GETAS DI ZONA SESAR KALIGARANG (KGFZ) SEMARANG: STUDI AWAL PENGAMATAN MIKROSTRUKTUR MENGGUNAKAN METODE PETROGRAFI - Fahrudin Fahrudin; Tri Winarno (TEKNIK, 2012)
Brittle deformation at Kaligarang fault zone result strain changes. That strain is microstructure.Microstructures can see closely petrography. That observation include grain form, microcrack can form atcontact point like Hertzian and diagonal intragranular microcracks. Grain forms over angular, straight, andconcoidal. Grain of crystal or lithic fragments floating at matrik or cements. Microcrack growth does not onlydepend on stress, but also on temperature and chemical environment, especially of the fluid in the crack.